2012
DOI: 10.1007/s00381-012-1949-8
|View full text |Cite
|
Sign up to set email alerts
|

Seizure and developmental outcomes after hemispherectomy in children and adolescents with intractable epilepsy

Abstract: Pathologic substrate was the main factor related with seizure outcome. In children with MCD and vascular lesions, although developmental progression is apparent, significant post-surgical improvements are restricted by the severity of pre-surgical neuropsychological disturbances and a slow maturation. Early surgery assessment is recommended to enhance the possibilities for a better quality of life in terms of seizure control, as well as better autonomy and socialization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 40 publications
0
22
0
11
Order By: Relevance
“…Some previous studies have found that seizure outcomes differ significantly with the underlying etiology, and that they are significantly worse in epilepsy patients with a developmental pathology than in those with an acquired pathology 7,11,16,17. In contrast, another study found no correlation between seizure outcome and etiology 12.…”
Section: Discussionmentioning
confidence: 89%
“…Some previous studies have found that seizure outcomes differ significantly with the underlying etiology, and that they are significantly worse in epilepsy patients with a developmental pathology than in those with an acquired pathology 7,11,16,17. In contrast, another study found no correlation between seizure outcome and etiology 12.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, a better outcome after surgery can be expected in patients operated on at a younger age and with a shorter duration of epilepsy [9]. Most studies have reported on seizure outcome after specific surgical procedures, such as temporal lobe resection [10,11] or hemispherectomy [12][13][14]. As clinicians, we meet children with medically intractable epilepsy and intellectual disabilities, but there are relatively few studies describing the cognitive outcome in unselected children with epilepsy severe enough to justify neurosurgery of any type, especially for the subgroup of children with a low IQ [6,9,15].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5,8,9,[17][18][19] We used data from the Nationwide Inpatient Sample (NIS) from 1988 to 2010 to extrapolate the national rate of hemispherectomy procedures over time and patient and hospital characteristics associated with in-hospital complications for patients undergoing these procedures to treat medically intractable epilepsy. To the authors' knowledge, this is the largest study to date evaluating trends in hemispherectomy performance and associated in-hospital complications.…”
mentioning
confidence: 99%